2000
DOI: 10.1175/1520-0477(2000)081<2179:atapps>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Terminal Area PBL Prediction System at Dallas–Fort Worth and Its Application in Simulating Diurnal PBL Jets

Abstract: A state-of-the-science meso-b-scale numerical weather prediction model is being employed in a prototype forecast system for potential operational use at the Dallas-Fort Worth International Airport (DFW). The numerical model is part of a unique operational forecasting system being developed to support the National Aeronautics and Space Administration's (NASA) Terminal Area Productivity Program. This operational forecasting system will focus on mesob-scale aviation weather problems involving planetary boundary l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
0
14
0
1
Order By: Relevance
“…Kaplan et al (2000) presented both observations and numerical model results indicating the structure of the LLJ in Dallas-Fort Worth, Texas. Berbery and Rasmusson (1999) further suggested that understanding how jet behavior is influenced by largescale flow patterns should help to reveal the role of large-scale climate variations in regulating regionaland continental-scale water budgets.…”
Section: Introductionmentioning
confidence: 89%
“…Kaplan et al (2000) presented both observations and numerical model results indicating the structure of the LLJ in Dallas-Fort Worth, Texas. Berbery and Rasmusson (1999) further suggested that understanding how jet behavior is influenced by largescale flow patterns should help to reveal the role of large-scale climate variations in regulating regionaland continental-scale water budgets.…”
Section: Introductionmentioning
confidence: 89%
“…This example also corresponds to a mean wind shear of around 5-6 m s −1 (100 m) −1 , assuming low surface wind speed. Similarly, in five casestudies from Dallas-Fort Worth International Airport, Kaplan et al (2000) showed that the average peak wind shear below the nocturnal jet was 2.9 m s −1 (100 m) −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The numerical model is MASS version 5.13 (Kaplan et al 2000). The MASS model is a hydrostatic terrain-following sigma coordinate system with comprehensive boundary layer and convective parameterizations (note table 1).…”
Section: Numerical Model and Postprocessormentioning
confidence: 99%